2015
DOI: 10.1016/j.bmcl.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Structure activity relationship of substituted 1,5-naphthyridine analogs of oxabicyclooctane-linked novel bacterial topoisomerase inhibitors as broad-spectrum antibacterial agents (Part-4)

Abstract: Bacterial resistance is rapidly growing, necessitating the need to discover new agents. Novel bacterial topoisomerase inhibitors (NBTIs) are new class of broad-spectrum antibacterial agents targeting bacterial DNA gyrase and topoisomerase IV. This class of inhibitors binds to an alternative binding site relative to fluoroquinolones and shows no cross-resistance to quinolones. NBTIs consist of three structural motifs. A structure activity relationship of the left hand motif 1,5-naphthyridine of oxabicyclooctane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…The (Table 1) however with detrimental effect on the hERG activity (13, IC 50 0.7 lM vs 2.0 lM, 3) consistent with the higher c log D. The next best compounds were found to be the hydroxy ethyl (15) and the hydroxy propyl (16) ethers with improved c log D (2.25 and 2.64) but with diminished hERG binding and functional activity associated with diminished P. aeruginosa activity.…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…The (Table 1) however with detrimental effect on the hERG activity (13, IC 50 0.7 lM vs 2.0 lM, 3) consistent with the higher c log D. The next best compounds were found to be the hydroxy ethyl (15) and the hydroxy propyl (16) ethers with improved c log D (2.25 and 2.64) but with diminished hERG binding and functional activity associated with diminished P. aeruginosa activity.…”
Section: Introductionsupporting
confidence: 70%
“…They did not show improvements in overall activity, spectrum and hERG profile other than compounds with an ether and a cyano group at C-2 with a halogen, hydroxy and a cyano at C-7. 15 We extended the study further and explored the ether substitution at C-2 with a fluoro substituent (one of the best substitutions for attenuation of hERG activity) at C-7 of the 1,5-napthyridine moiety. This Letter describes the synthesis and SAR of the C-2 ether substituted C-7 fluoro-1,5-naphthyridine of the oxabicyclooctane linked NBTIs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecules that inhibit hERG potassium channel lead to QT interval prolongation and sudden death. In the previous reports we have described modifications on all three structural moieties of NBTIs: left-hand side (LHS) (15,16), right-hand side (17), and linker (18). We found that maximal modulation of the hERG activity was achieved from modifications of the DNA binding motif of the left-hand-side moiety, particularly introduction of a hydroxy tricyclic group (e.g., Fig.…”
mentioning
confidence: 98%
“…14 In order to maintain Gram-negative activity and spectrum, we focused our SAR study on the both series. Recently we reported SAR around the LHS 1,5-naphthyridine 15,16 and hydroxy tricyclic 1,5-naphthyridinone, 14 as well as a survey of RHS moieties applicable to the hydroxy tricyclic series. 17 This Letter focuses on the synthesis and SAR of pyridoxazinone-substituted oxabicyclooctane linked NBTIs along with the defining an understanding of the role of the NH at position-7 of the linker.…”
Section: Introductionmentioning
confidence: 99%